Penafsiran Ayat-ayat Haji dalam Tafsir Al-Munir - Safria Andy; Ghita Kinanti Pratiwi Sembiring; Wildan Hamdani Nasution (ISLAMIKA, 2023)
Al-Qur'an and hadith which are the main basis are always solutions to the problems of the people, both in terms of worship and muamalah. The purpose of writing this article is to find out how to interpret the verses about the pilgrimage through Al-Munir's interpretation using the literary method, where the data collected uses the form of scientific literature books relating to the discussion in this study. The data source used in this research is Al-Munir's interpretation. The results of the study explain that the interpretation of the verses of the pilgrimage in Al-Munir's interpretation is based on QS. Al-Hajj verses 26-29 that is only servants who are able to go to Baitullah are obliged to perform the pilgrimage. The actual ability has developed into one of the prerequisites for performing the pilgrimage. Then it is permissible to do business on the way to remember Allah SWT, especially in order to give thanks for the favors that Allah has given by reciting tasbih and takbir sentences over the food that has been provided in the form of cows, goats and camels.